2008
DOI: 10.1108/00346650810863028
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of sourdough bread using a blend of bacterial culture and baker's yeast

Abstract: PurposeWheat is the staple food in many parts of the world and bread is one of the most important products of wheat flour. There is a need for innovations in bread making to increase its shelf life and consumer's attraction. Fermentation is mostly done by yeast but it does not produce appreciable amounts of organic acids, which are required to enhance the shelf life of bread. The present study aims to determine the effect of bacterial and yeast culture blends on the quality and shelf life of sourdough bread an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…During the evaluation of yoghurts produced with mix commercial cultures and yoghurts produced with strains of L. plantarum it was observed that there was no significant difference amongst the sensory properties of these products (Modzelewska-Kapituła, Kłę bukowska, & Kornacki, 2008). A soymilk-based yoghurt known as "sogurt" fermented with lactobacilli strains including L. plantarum, has appeared as an option to the traditional dairy-based yoghurts having good consumer acceptability (Anjum, Pasha, Ghafoor, Issa Khan, & Ali Raza, 2008). With these results we can state that L. plantarum can be further exploited to develop non-conventional probiotic beverages with an acceptable flavour.…”
Section: Acceptance Of Functional Cereal Beveragesmentioning
confidence: 91%
“…During the evaluation of yoghurts produced with mix commercial cultures and yoghurts produced with strains of L. plantarum it was observed that there was no significant difference amongst the sensory properties of these products (Modzelewska-Kapituła, Kłę bukowska, & Kornacki, 2008). A soymilk-based yoghurt known as "sogurt" fermented with lactobacilli strains including L. plantarum, has appeared as an option to the traditional dairy-based yoghurts having good consumer acceptability (Anjum, Pasha, Ghafoor, Issa Khan, & Ali Raza, 2008). With these results we can state that L. plantarum can be further exploited to develop non-conventional probiotic beverages with an acceptable flavour.…”
Section: Acceptance Of Functional Cereal Beveragesmentioning
confidence: 91%
“…The aroma of breads was also more desirable in those made of doughs developed with the I-stage than with the II-stage method. In contrary, the results of Robert et al [20], Faqir et al [21] and Jayaram et al [22] showed better sensory properties of breads with sourdough addition comparing to only yeast-fermented samples. The breads made of the 450-type flour were scored significantly higher for general appearance than these made of the 1650-type flour.…”
Section: Resultsmentioning
confidence: 83%
“…The bread making was carried out according to Plessas et al [17] with slight modification, briefly the base recipe is 400 g flour, 200 g sourdough (50% w/w on flour basis), 6 g salt (1.5% w/w on flour basis) and 200 mL tap water were kneaded for 15 min. The dough rising were carried out at 30 ºC for 2 hours.…”
Section: Bread Makingmentioning
confidence: 99%
“…Furthermore the sourdough fermentations enhance dough properties and improve volume, texture, flavor, and nutritional value of the bread and not least protect bread from mould and bacterial spoilage [2,14,15,16]. The sourdough fermentation is traditionally a spontaneous process, the microorganisms originate from flour, dough ingredients or the environment, but the microbial composition is especially influenced by the bakery environment [11,17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation